Social inequality, health behaviour determinants and health behaviour: a systematic review : registered report - Hilz, Lisa Karla; Jones, Christopher; Conner, Mark; Jürgens, Dorothee; Pedrós Barnils, Núria; Schüz, Benjamin (Psychology & health, 2025)
Health inequalities are partly due to social differences in health behaviours, but we know little about the underlying mechanisms. Health behaviour theories, summarised e.g. in the Theoretical Domains Framework (TDF) may outline such mechanisms. Two pathways have been theorised: Behavioural determinants mediate social differences in behaviour, and social differences in the determinants-behaviour relationship (moderation). Here, we summarise the literature on both pathways. Systematic review of observational studies predicting health behaviour from TDF variables with either mediation of inequality indicators (based on PROGRESS-Plus) through TDF determinants or moderation of TDF determinants effects by PROGRESS-Plus facets. 86 reports with 109 studies were included. Studies were summarised in an evidence synthesis with harvest plots. The most frequently examined determinants were competence beliefs, consequence beliefs, and emotions. Evidence was found for both, mediated effects of inequality indicators via TDF domains and moderating effects of inequality indicators on TDF-behaviour associations, but the majority of studies found no significant effects for either. Effects of determinants on health behaviour may be moderated by inequality indicators, and determinant may serve as mediators in the relationship between indicators of inequality and health behaviour. However, heterogeneity in all findings suggest the need for more systematic research.
Gesehen am 12.01.2026